Introduction and some uses of QR codes - Leiva-Aguilera, Javier (Anuario ThinkEPI, 2012)
QR codes are an easy way to read information from mobile devices and allow direct or indirect access to information resources. For libraries, these codes can help to expand services and access to mobile users in simple and inexpensive ways: resource guides, practical information, direct download of documentation, multimedia, etc. The article provides examples of use and tools for building codes.
Keywords: QR codes; Mobile web; Mobile services.